2018
DOI: 10.1089/jop.2017.0138
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Netarsudil Ophthalmic Solution on Aqueous Humor Dynamics in a Randomized Study in Humans

Abstract: Purpose: Netarsudil, an inhibitor of Rho kinase and a norepinephrine transporter, has been shown to lower elevated intraocular pressure (IOP) in controlled studies of patients with open-angle glaucoma and ocular hypertension, and in healthy volunteers. The mechanism of this ocular hypotensive effect in humans is unknown.Methods: The objective of this study was to evaluate the effect of netarsudil 0.02% on aqueous humor dynamics (AHD) parameters. In this double-masked, vehicle-controlled, paired-eye comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 33 publications
1
88
0
3
Order By: Relevance
“…Percentages are based on the number of patients (n) in a given treatment group for the safety population AE treatment emergent adverse event In the system organ class or preferred term, n is the number of patients with at least one adverse event; % is based on the number of patients (n) in a given treatment group for the safety population When reporting incidence, a patient was only counted once if they ever experienced an event within the system organ class or individual preferred term. System organ class and preferred term are based on Version 19.0 of the MedDRA coding dictionary DISCUSSION Netarsudil, a ROCK inhibitor, reduces IOP by novel mechanisms of action that lead to increased trabecular outflow [12][13][14][15][16]18]. In preclinical and human studies, the distinct mechanism of action of netarsudil has been demonstrated to involve increasing trabecular outflow by decreasing actomyocin-driven cellular contraction and reducing production of extracellular matrix proteins [12,19].…”
Section: Safetymentioning
confidence: 99%
See 3 more Smart Citations
“…Percentages are based on the number of patients (n) in a given treatment group for the safety population AE treatment emergent adverse event In the system organ class or preferred term, n is the number of patients with at least one adverse event; % is based on the number of patients (n) in a given treatment group for the safety population When reporting incidence, a patient was only counted once if they ever experienced an event within the system organ class or individual preferred term. System organ class and preferred term are based on Version 19.0 of the MedDRA coding dictionary DISCUSSION Netarsudil, a ROCK inhibitor, reduces IOP by novel mechanisms of action that lead to increased trabecular outflow [12][13][14][15][16]18]. In preclinical and human studies, the distinct mechanism of action of netarsudil has been demonstrated to involve increasing trabecular outflow by decreasing actomyocin-driven cellular contraction and reducing production of extracellular matrix proteins [12,19].…”
Section: Safetymentioning
confidence: 99%
“…System organ class and preferred term are based on Version 19.0 of the MedDRA coding dictionary DISCUSSION Netarsudil, a ROCK inhibitor, reduces IOP by novel mechanisms of action that lead to increased trabecular outflow [12][13][14][15][16]18]. In preclinical and human studies, the distinct mechanism of action of netarsudil has been demonstrated to involve increasing trabecular outflow by decreasing actomyocin-driven cellular contraction and reducing production of extracellular matrix proteins [12,19]. Netarsudil was also shown to decrease episcleral venous pressure [12,18,19].…”
Section: Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…Even though dysfunction of the trabecular outflow pathway is responsible for elevated IOP, clinically, most of IOP-lowering medications target the unconventional outflow pathway or secretion. New medications targeting the predominant drainage pathway (the TM pathway) are in high demand, including two recently approved medications (8, 12, 13). Thus, rho kinase inhibitors and nitric oxide drugs are the results of research over the last 25 years that identified important regulatory processes in the trabecular outflow pathway (8).…”
Section: Introductionmentioning
confidence: 99%